2016
DOI: 10.1371/journal.pone.0161100
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Four Chimeric Trypanosoma cruzi Antigens Based on Antigen-Antibody Detection for Diagnosis of Chronic Chagas Disease

Abstract: The performance of serologic tests in chronic Chagas disease diagnosis largely depends on the type and quality of the antigen preparations that are used for detection of anti-Trypanosoma cruzi antibodies. Whole-cell T. cruzi extracts or recombinant proteins have shown variation in the performance and cross-reactivity. Synthetic chimeric proteins comprising fragments of repetitive amino acids of several different proteins have been shown to improve assay performances to detect Chagasic infections. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(96 citation statements)
references
References 43 publications
(41 reference statements)
4
79
1
Order By: Relevance
“…A study in Argentina, for instance, performed in a co-endemic area for leishmaniasis and chronic CD, reported 81.8% (9/11) cross-reactivity using conventional ELISA [51]. A more recent study confirmed this elevated cross-reaction rate and verified a relatively large number of inconclusive results (2.9–8.6%) using conventional and non-conventional tests [9]. Contrary to these data, IBMP-8.1 chimera cross-reacted with two samples and IBMP-8.3 and -8.4 with one sample, demonstrating very little positivity in 153 sample of Leishmania spp.…”
Section: Discussionmentioning
confidence: 96%
“…A study in Argentina, for instance, performed in a co-endemic area for leishmaniasis and chronic CD, reported 81.8% (9/11) cross-reactivity using conventional ELISA [51]. A more recent study confirmed this elevated cross-reaction rate and verified a relatively large number of inconclusive results (2.9–8.6%) using conventional and non-conventional tests [9]. Contrary to these data, IBMP-8.1 chimera cross-reacted with two samples and IBMP-8.3 and -8.4 with one sample, demonstrating very little positivity in 153 sample of Leishmania spp.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, chimeric proteins have been proposed to improve the assay's accuracy to diagnose CD. Recently, a phase I study was performed with 4 chimeric proteins from the Instituto de Biologia Molecular do Paraná (IBMP-8.1, 8.2, 8.3, and 8.4) to detect specific anti-T. cruzi antibodies using both ELISA and LMA (15), demonstrating that each antigen accurately discriminated CD-positive from CD-negative samples. In addition, no significant differences were observed with respect to the diagnostic performances of the ELISA and LMA test methods.…”
mentioning
confidence: 99%
“…[90] Various strategies for diagnosis of Chagas disease and trypanosomiasis using electrochemical biosensors have been reported. [61,62,[91][92][93][94][95][96][97] Diniz et al [91] adsorbed a polypeptide chain formed by recombinant antigens, cytoplasmic repetitive antigen and flagellar repetitive antigen of Trypanosoma cruzi, onto an oxidized gold electrode, and the interaction with sera from chronic chagasic patients was monitored by electrochemical impedance spectroscopy. More recently, Ferreira et al [62] used T.cruzi proteins from epimastigote membranes for the construction of an amperometric immunosensor for serological diagnosis of Chagas' disease.…”
Section: Electrochemical Affinity Biosensors For Detection Of Ntds Camentioning
confidence: 99%
“…An immunosensor for anti-T.cruzi was developed by immobilization the antigen and EIS measurement of antibody interaction. [95] Qualitative diagnosis of Chagas' disease for verifying the presence or the absence of T cruzi using a simple configuration was also proposed by Santos et al [96,97] Direct detection of the immunoreaction was performed by EIS after immobilization of the antigen onto a gold electrode modified with a MPA selfassembled monolayer (SAM). Recently, a sandwich immunosensor for anti-IgM T. cruzi-specific antibodies, which are a biomarker for congenital Chagas disease was also reported.…”
Section: Electrochemical Affinity Biosensors For Detection Of Ntds Camentioning
confidence: 99%